ChemInform Abstract: RhIII‐Catalyzed Dehydrogenative Coupling of Quinoline N‐Oxides with Alkenes: N‐Oxide as Traceless Directing Group for Remote C—H Activation. Issue 14 (March 2016) - Sharma, Ritika; Kumar, Rakesh; Kumar, Inder; Sharma, Upendra
Abstract: A dehydrogenative coupling of quinoline N‐oxides with alkenes provides C(8)‐olefinated quinoline derivatives by a remote C—H activation strategy.